Eksplorasi Nilai Tradisi pada Konsep Desain Kaos Gandrung Lombok - Sasih Gunalan; Susi Handayani; Haryono Haryono; I Nyoman Miyarta Yasa (Jurnal SASAK : Desain Visual dan Komunikasi, 2021)
ABSTRACTThe development of t-shirt design in this decade cannot be separated from how the development and cultural identity in which the design work is presented. Design exploration with a combination of locality values ​​has become an important issue for design products in several t-shirt outlets in Lombok, one of which is Gandrung Lombok. The concept of regional culture became the thematic for the Gandrung Lombok t-shirt design, in addition to other themes. The purpose of this study is focuse on exploring the value of tradition in the concept of Gandrung Lombok t-shirt design as a representation of local cultural values ​​reflected in t-shirt design works on the market. This research uses naturalistic qualitative research methods, by extracting data with natural settings that occur in the field. In this study, findings can befound in the form of Gandrung Lombok designers, who have a strong awareness of making local cultural identities the subject matter of their t-shirt design works in the market. There is an exploration of concepts and ideas in every existing t-shirt design. The exploration in question is changed in two patterns, namely deformation (addition) and stylization (reduction) of shape with a mix of pop colors. Some of the thematics in the design of the Gandrung Lombok t-shirt are, sasak flute blower, drum beleq, songket weaving motifs and mask craft designs. Overall, the elements and ideas for creating the Gandrung Lombok t-shirt design with the theme of tradition are rooted in local activities and culture, namely Lombok culture.